Acetyl- and O-alkyl- derivatives of β-mangostin from Garcinia mangostana and their anti-inflammatory activities - Karunakaran, Thiruventhan; Ee, Gwendoline Cheng Lian; Intan Safinar, Ismail; Siti Mariam, Mohd Nor; Nor Hisam, Zamakshshari (Taylor & Francis, 2018)
Pure β-mangostin (1) was isolated from the stem bark of Garcinia mangostana L. One monoacetate (2) and five O-alkylated β-mangostin derivatives (3–7) were synthesised from β-mangostin. The structures of these compounds were elucidated and determined using spectroscopic techniques such as 1D NMR and MS. The cytotoxicities and anti-inflammatory activities of these five compounds against RAW cell 264.7 were tested. The structural-activity relationship studies indicated that β-mangostin showed a significant activity against the LPS-induced RAW cell 264.7, while the acetyl- as well as the Oalkyl- β-mangostin derivatives did not give good activity. Naturally occurring β-mangostin demonstrated comparatively better antiinflammatory activity than its synthetic counterparts.